Virtual team performance research: a bibliometric analysis using VOSviewer - Alkoud, Saleh; Zainudin, Dolhadi; Mhd. Sarif, Suhaimi (Human Resource Management Academic Research Society (HRMARS), 2024)
The study aims to use bibliometric analysis to highlight worldwide research patterns and future directions for virtual team performance during the last three decades (1996–2024). The study employs bibliometric analysis to examine co-authorship, co-occurrence, citation, bibliographic coupling, and co-citation analysis in 180 articles extracted from the Scopus database. It does this by using performance analysis and scientific mapping. The most prolific authors, the most significant papers, countries, and organizations were examined, as well as the volume of scientific publications. VOSviewer was employed in the study as a performance analysis and science mapping tool. The most productive years were 2012, 2022, and 2023, with 15 publications for each. And the most impactful institutes and countries are the University of North Carolina in the USA, and the country is France, respectively. Similarly, the most influential journal is “Academy of Management Journal”, furthermore, the most cited article is “The impact of team empowerment on virtual team performance: The moderating role of face-to-face interaction." The study also identified three thematic clusters of research on virtual team performance; the three theme groupings are virtual team, virtual team performance, and geographically distributed team. The present study offers an overview of recent research on the performance of virtual teams. It also suggests possible lines of inquiry for additional research in this field. The current research contributes to filling the knowledge gaps in current studies on the performance of virtual teams through a comprehensive review using bibliometric analysis.